JUSTICE AND THEOLOGY OF KANT'S PRACTICAL PHILOSOPHY - Nerija Putinaitė (Problemos)
The paper deals with the problem of justice in Kant's practical philosophy. In the realm of philosophy of Kant the problem of justice is distinguished by the lack of interest from the side of historians of philosophy and philosophers. The paper is an example of an attempt to deal with the problem of justice in the context of Kant's practical theory. The concept of ultimate practical end is the central for Kant's theory of morals and law. It could be treated as the most important for the inquiry into the problem of justice. The concepts of compulsion, the natural and civil state, the capital punishment and the principal of equality are the most significant guides to our research. The paper also indicates the limits of strict moral interpretation of the concept of justice. It also makes some references to further investigation.